KAJIAN PERTIMBANGAN PENENTUAN LOKASI SEKOLAH (STUDI KASUS SMKN 1 GEGER KABUPATEN MADIUN) - SIGIT WIDODO, BAMBANG (Pendidikan Geografi, 2014)
Abstrak. This research aims to know the description of: 1) how the consideration of determining the location and school building, and 2)  how the development of school. The research approach is qualitative by case study plan. The procedure of data collection is done by : (1) in-depth interview, (2) participative observation and (3) document study. The data analysis are consisted of: (1) data reduction, (2) data display, and (3) conclusion. But, the data approval check uses credibility, transferability, dependability, and confirmatablity. The finding of those three location show that : (1) the consideration of determining location and building school based on the social need, and (5) the development of school which is observed from the numbers of students, school building, skills program, school achievement and partnerships between schools and external institution has increased, bocause the support and commitment from the district / city and community.   Keywords: consideration, school location, development of school.